A quantile regression analysis of international financial integration-economic growth nexus - Abdul Rahman, Mazlina; Ibrahim, Saifuzzaman; Wan Ngah, Wan Azman Saini (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2015)
This study aims to examine the relationship between international financial integration (IFI) and economic growth for countries with different level of economic development. Adopting the quantile regression technique on cross sectional data of 73 countries, the results show that IFI has a positive impact on economic growth. However, the impact does not exist in countries where the economic development are too low or in highly developed countries.